RATIONAL ORGANIZATIONAL AND TECHNOLOGICAL DECISIONS ON THE GRAIN STORAGES CONSTRUCTION OR RENOVATION SITES - Nikiforov, A. L. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article presents a method for choosing rational organizational and technological decisions at the grain storages construction or reconstruction sites using the results of the author's experimental and theoretical studies. It is given conditions analysis for the investigated enterprises operational activity. The obtained experimental statistical dependencies of the indicators change of such operational activity from the varied organizational and technological factors and the developed algorithms allow choosing rational organizational and technological decisions for the elevators construction and reconstruction based on the construction site conditions analysis and on the effective planning.